Deconstructing Radical Interpretations: A Contextual Analysis of War-Related Hadith and Their Modern Implications - Rahman Rahman; Syamsuddin Muir; Suhaimi Suhaimi; Muhammad Hafiz; Usman Usman; Wasalmi Wasalmi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study examines a contextual interpretation of hadiths related to war, moving beyond literalist readings that often detach the texts from their historical, social, and ethical dimensions. Methodologically, the research employs qualitative textual analysis combined with hadith hermeneutics and a historical-critical approach, supported by a maqasid al-sharia framework. The study focuses on a selected corpus of approximately 60–70 narrations concerning warfare, particularly the well-known hadith about the command to fight people until they profess the testimony of faith, drawn from major canonical collections such as Sahih al-Bukhari, Sahih Muslim, Sunan al-Tirmidhi, Sunan al-Nasa’i, and Musnad Ahmad. These narrations are analyzed through thematic coding to identify patterns of literalist versus contextual interpretation, while also examining their linguistic structures, historical backgrounds, and legal-ethical implications. The findings indicate that literal interpretations, when detached from context, may contribute to rigid and exclusivist understandings that can be misused in contemporary discourse. In contrast, a contextual approach demonstrates that hadiths on war emerged within specific circumstances of defense, conflict regulation, and the survival of the early Muslim community, rather than as universal mandates for violence. By integrating linguistic analysis, historical contextualization, and the objectives of Islamic law, this study shows that these texts can be understood as ethical guidance for limiting conflict and promoting justice and peaceful coexistence. This research contributes to contemporary hadith studies by offering a systematic methodological framework that bridges classical interpretive tools and modern hermeneutical approaches, while also supporting more balanced and responsible religious understanding in plural and modern societies.